2018
DOI: 10.1177/0972262917750246
|View full text |Cite
|
Sign up to set email alerts
|

Using New Case Studies for Evaluation of Marketing Student’s Academic Performance

Abstract: Case method has been a popular pedagogy in management education. It is a preferred evaluation tool which is inherently subjective in nature. This article compares the results of case-based evaluation in marketing discipline, in announced and unannounced settings, for full-time and part-time management programmes and discusses its implications. The data were collected from the formal evaluation made by a faculty of an Association of MBAs (AMBA) accredited management institute of India. The results suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Today the case study method is a factor in increasing the competence of teachers and a productive method for developing the professional qualities of economics students (Zhakshylykova, 2017). The analysis of the use of case studies in entrepreneurship education is much more actively studied abroad (Drake, 2019;Mukherjee, 2018;Prado et al, 2019;Yao & Collins, 2018), which is probably International Journal of Instruction, October 2021 • Vol.14, No.4 associated with a longer tradition of teaching entrepreneurship due to the market economy system compared to the Russian Federation.…”
Section: Discussionmentioning
confidence: 99%
“…Today the case study method is a factor in increasing the competence of teachers and a productive method for developing the professional qualities of economics students (Zhakshylykova, 2017). The analysis of the use of case studies in entrepreneurship education is much more actively studied abroad (Drake, 2019;Mukherjee, 2018;Prado et al, 2019;Yao & Collins, 2018), which is probably International Journal of Instruction, October 2021 • Vol.14, No.4 associated with a longer tradition of teaching entrepreneurship due to the market economy system compared to the Russian Federation.…”
Section: Discussionmentioning
confidence: 99%
“…A case study explains a phenomenon and enhances our understanding of various people, groups, communities, and organizations (Mukherjee, 2018). This case study is designed to emphasize an in-depth investigation of the entrepreneurial competencies of entrepreneurs in Cameroon.…”
Section: Methodsmentioning
confidence: 99%
“…There is a positive and direct relationship between the case-based learning approach and the four aspects of student engagement, suggesting that case-based learning results in increased behavioral, emotional, and cognitive engagement for students (Raza et al, 2020). Mukherjee (2018) compared the results of a case-based evaluation in the marketing discipline for full-and part-time management programs and discussed the implications. The results showed that for full-time programs, the relative scores to assess each evaluation component would likely be a more robust evaluation mechanism than using only grades or using combined scores for the final assessment.…”
Section: Case-based Learningmentioning
confidence: 99%